The effect of involvement on attitude formation and strength in the digital domain - Palla, Polyxeni Jenny; Kyriacou, Evdoxia; Zarkada, Anna K. (My University, 2022)
The spike in e-commerce caused by COVID-19 mandates a re-evaluation of the Elaboration Likelihood Model (ELM) vis-à-vis digital marketing communications. The experiment presented here focuses on product involvement on attitude formation and strength. A sample of 185 students was exposed to mock websites of fictitious high- and low- involvement products (a laptop and a soft drink) chosen through a free-association exercise with the involvement level measured using two independent samples of 20 and 30 students respectively. Exposure to the high involvement product website elicited a greater number of product- and website-related thoughts (central route processing) than exposure to the low involvement one (peripheral route processing). Involvement was found to influence attitude formation, but it did not affect attitude strength (measured at a later time after a single exposure). The efficacy of the measurement scales and the applicability of the ELM to the digital domain are confirmed but e-commerce marketers are advised to encourage the constantly connected 21st century consumers to regularly revisit their website to strengthen the attitudes their Marcoms have formed. Further research is required to further elucidate the changes to consumers’ cognitive processes that were brought about by the COVID-19 lockdown-imposed switch to e-commerce and assess their stability.
Keywords: Online cognitive process; Experimental design; Elaboration Likelihood Model; Attitude strength; Product-class involvement; Thought elicitation